2019
DOI: 10.29103/ijevs.v1i7.2571
|View full text |Cite
|
Sign up to set email alerts
|

Improving Students' Mathematical Critical Thinking Abilities Through the Problem Solving Method on the Sequences and Series Course

Abstract: This study aims to determine the improvement of students' mathematical critical thinking abilities through problem solving methods. This study was hold at MAN 3 Bireuen (High School Level) in the 2019/2020 school’s year. The research method was a quasi-experimental study design nonrandomized Pre-test Post-test Control Group Design. The population of the study were all students of Class XI MAN 3 Bireuen with purposive sampling technique. The study sample was to 30 students for the experimental class and 28 stud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…At the level they are applying, students are also in the medium category with a value of 46.624%, but the value is still below 50%. At the last level of reasoning, students still have difficulty solving problems that require reasoning ability, which is also one of the higher-order thinking skills (Dahliana et al, 2019;Marhami, Rohantizani, et al, 2020). It is shown in the average score obtained, which is a percentage of 39.76% in the low category.…”
Section: Resultsmentioning
confidence: 98%
“…At the level they are applying, students are also in the medium category with a value of 46.624%, but the value is still below 50%. At the last level of reasoning, students still have difficulty solving problems that require reasoning ability, which is also one of the higher-order thinking skills (Dahliana et al, 2019;Marhami, Rohantizani, et al, 2020). It is shown in the average score obtained, which is a percentage of 39.76% in the low category.…”
Section: Resultsmentioning
confidence: 98%
“…Normalized gain or N-Gain Score aims to determine the effectiveness of the use of a particular method or action in the one group pre-test post-test design research (Dahliana et al, 2019). The N-Gain Score test is done by calculating the difference between the pretest and posttest scores (Lestari et al, 2018).…”
Section: N-gain Value Analysismentioning
confidence: 99%
“…The Effect Size of PBL on Students' MCTS Based on Treatment Duration Figure 4 shows that there were 13 literature in which its PBL treatment duration was less than or equals 1 month. From these literatures, six literatures reported that PBL had a moderate effect on students' MCTS (Ayuni et al, 2021;Dahliana et al, 2019;Haerani et al, 2019;Prihono & Khasanah, 2020;Tunjungsari & Tasyanti, 2017;Yolanda, 2019). Moreover, six other literature reported that PBL had a strong effect on students' MCTS (Gunur et al, 2019;Hamid & Lambertus, 2014;Jumaisyaroh et al, 2014Jumaisyaroh et al, , 2015Nugraha & Mahmudi, 2015;Umar et al, 2020).…”
Section: Figurementioning
confidence: 99%